THEORETICAL ACCOUNTING OF MATERIAL RESOURCES - Alimkhanova Nigora Alimkhanovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article is devoted to the theoretical basis of reflecting the relations related to inventory in business entities of different types of ownership operating in our country in accounting. The types of inventories in business entities, the main tasks of the accountant in accounting for them, as well as opinions on the state of inventory and the establishment of internal control over their storage are highlighted. To fulfill these tasks, first of all, a proposal and recommendations on the use of primary accounting data, synthetic and analytical account registers were developed. This eliminates several problems in the organization of inventory accounts in economic entities and serves to increase the level of accuracy of financial reporting data